Design of The Mechanism for Auto Release Seat Belt in End-Button Release Buckle - Abdul Aziz, Muhammad Aidil Safwan; Mohmad Jaat, Norrizam; Mohamed, Norirda; Azhar, Azizi Hakimi (Journal of Automotive Powertrain and Transportation Technology, 2023)
This project revolves around the buckle of a seat belt, mainly push end release button type, where a feature was created to make it into an auto release seat belt through designing the mechanism within the buckle. The aim of the project is to design the mechanism part of a convertible end button release seat belt buckle, to simulate the designed mechanism part of the convertible auto release seat belt for vehicle cars and to analyze the designed mechanism regarding the effectiveness when installed. 3 different models of solenoid-triggered-parts were designed where Model 1 has no support on its side, presence of fillet and smallest surface area for the base. As for Model 2 and 3, there were no fillet used, presence of support of the side and Model 2 has larger surface area for the base, but Model 3 has the largest amongst the three models. The parameter of this project was the material used when running the simulation which is Polyphenylene Ether (PPE). Through the simulation results, a final model was designed consists of features such as, having support on the side, largest surface area for the base and presence of fillet as these features has shown the best results through the simulation. As for the conclusion, the study managed to achieve all of the objectives which are, the auto release mechanism was designed and simulated successfully using SolidWorks, and it was simulated through simulation within the software.